Minat Baca dan Faktor yang Mempengaruhinya pada Siswa Kelas V Sekolah Dasar - Hani Muslihatun Zahro; Varenezza Prastika; Suherli Kusmana (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Reading interest is one of the important factors determining students’ learning success in elementary schools. However, various surveys indicate that students' reading interest in Indonesia remains relatively low. This study aimed to describe the reading interest of fifth-grade students at SDN 1 Purwawinangun Cirebon, identify the internal and external factors influencing it, and describe teachers’ efforts to improve students’ reading interest. This research employed a descriptive qualitative approach involving one fifth-grade teacher and 34 fifth-grade students. Data were collected through questionnaires, observations, semi-structured interviews, documentation, and field notes. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, and member checking. The findings revealed that students’ reading interest tended to be moderate to low. The utilization of reading facilities obtained the lowest score (53.04%), while awareness of the benefits of reading achieved the highest score (83.21%). Internal factors influencing reading interest included intrinsic motivation, reading attention, and enjoyment of reading. External factors included family support, teachers, peers, school facilities, and gadget usage. Teachers have implemented various efforts such as reading habituation programs, classroom reading corners, literacy activities, and reading motivation strategies. This study recommends strengthening collaboration between schools and families and developing more structured literacy programs to enhance elementary students’ reading interest.